2016
DOI: 10.1016/j.cognition.2016.04.005
|View full text |Cite
|
Sign up to set email alerts
|

What is automatized during perceptual categorization?

Abstract: An experiment is described that tested whether stimulus-response associations or an abstract rule are automatized during extensive practice at perceptual categorization. Twenty-seven participants each completed 12,300 trials of perceptual categorization, either on rule-based (RB) categories that could be learned explicitly or information-integration (II) categories that required procedural learning. Each participant practiced predominantly on a primary category structure, but every third session they switched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 55 publications
1
19
0
Order By: Relevance
“…It is thus not the right model for cultural heuristics that have important directional components. In this kind of situation, simple "if-then" rules may be a more appropriate algorithmic approach to consider (Kruglanski and Gigerenzer 2011;Roeder and Ashby 2016). Another relevant algorithmic approach is Bayesian modeling, which has successfully been used to model inferences in a broad range of domains and is a rich area of investigation in contemporary cognitive science (Tenenbaum et al 2011;Tenenbaum, Griffiths, and Kemp 2006).…”
Section: Implications Of Clarified Network-of-associations Modelmentioning
confidence: 99%
“…It is thus not the right model for cultural heuristics that have important directional components. In this kind of situation, simple "if-then" rules may be a more appropriate algorithmic approach to consider (Kruglanski and Gigerenzer 2011;Roeder and Ashby 2016). Another relevant algorithmic approach is Bayesian modeling, which has successfully been used to model inferences in a broad range of domains and is a rich area of investigation in contemporary cognitive science (Tenenbaum et al 2011;Tenenbaum, Griffiths, and Kemp 2006).…”
Section: Implications Of Clarified Network-of-associations Modelmentioning
confidence: 99%
“…Humans can improve their performance in any task by gradually optimizing the implementation of a known strategy, or by devising and then adopting novel, more efficient strategies (Badre et al, 2010;Collins & Frank, 2013;Donoso et al, 2014;Heathcote et al, 2000;Roeder & Ashby, 2016;Schuck et al, 2015). Previous research has shown that practicing a task induces changes not only in the activation level of specific brain regions, but also in the long-range organisation of the relevant brain networks (Bassett & Mattar, 2017;Bassett et al, 2015;Chein & Schneider, 2005;Cole et al, 2013;Patel et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, one can spontaneously learn about potentially useful contingencies in the task (e.g. new stimulusresponse associations), use this new information to devise a new strategy based on a different algorithm, and then switch to it, thus reaching the same task goals with greater efficiency (Badre, Kayser, & D'Esposito, 2010;Cohen, McClure, & Yu, 2007;Cole, Braver, & Meiran, 2017;Collins & Frank, 2013;Donoso, Collins, & Koechlin, 2014;Hayden, Pearson, & Platt, 2011;Heathcote, Brown, & Mewhort, 2000;Roeder & Ashby, 2016;Schuck et al, 2015;Wenke, De Houwer, De Winne, & Liefooghe, 2015). Task optimization has been associated with a decrease of activation both in areas specialized for the task and in a set of brain regions associated to control and attentional functions (Chein & Schneider, 2005;Hampshire et al, 2016;Patel, Spreng, & Turner, 2013).…”
mentioning
confidence: 99%
“…Despite their similarities, there is good evidence for at least some qualitative differences. For example, Roeder and Ashby (2016) reported evidence that SR mappings are automatized after extensive II training, whereas rules are automatized in RB tasks. Participants in this study completed more than 12,000 trials of RB or II categorization distributed across 21 different training sessions.…”
Section: Automaticitymentioning
confidence: 99%